[tex]\vec r(t)=\langle6t,1+3t,4t\rangle[/tex]
[tex]\vec R(s)=\langle2+s,-8+3s,-12+4s\rangle[/tex]
Take the derivatives of each to get the tangent vectors:
[tex]\dfrac{\mathrm d\vec r(t)}{\mathrm dt}=\langle6,3,4\rangle[/tex]
[tex]\dfrac{\mathrm d\vec R(s)}{\mathrm ds}=\langle1,3,4\rangle[/tex]
Take the cross product of the tangent vectors to get a vector that is normal to both lines:
[tex]\langle6,3,4\rangle\times\langle1,3,4\rangle=\langle0,-20,15\rangle[/tex]
The two given lines intersect when [tex]\vec r(t)=\vec R(s)[/tex]:
[tex]\langle6t,1+3t,4t\rangle=\langle2+s,-8+3s,-12+4s\rangle\implies t=1,s=4[/tex]
that is, at the point (6, 4, 4).
The line perpendicular to both of the given lines through the origin is obtained by scaling the normal vector found earlier by [tex]\tau\in\Bbb R[/tex]; translate this line by adding the vector [tex]\langle6,4,4\rangle[/tex] to get the line we want,
[tex]\vec\rho(\tau)=\langle6,4,4\rangle+\langle0,-20,15\rangle\tau[/tex]
[tex]\boxed{\vec\rho(\tau)=\langle6,4-20\tau,4+15\tau\rangle}[/tex]